1987
DOI: 10.3168/jds.s0022-0302(87)80254-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yeast Culture and Aspergillus oryzae Fermentation Extract on Ruminal Characteristics and Nutrient Digestibility

Abstract: Four nonpregnant and nonlactating Holstein cows fitted with ruminal fistulas were assigned to each of four diets in a 4 X 4 Latin square design. Dietary treatments were 1) basal diet containing 50% concentrate; 2) basal diet plus 90 g/d yeast culture; 3) basal diet plus 2.63 g/d Aspergillus oryzae fermentation extract; 4) basal diet plus 90 g/d of A. oryzae fermentation extract and yeast culture. Cows were fed diets at a rate of 86 g DM/kg BW.75 for 14 d adaptation followed by an 8-d collection period. Digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
134
4
18

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(176 citation statements)
references
References 9 publications
20
134
4
18
Order By: Relevance
“…Some reports have demonstrated no effects of yeast culture supplementation on ruminal pH, rumen ammonia concentration, and VFA patterns in vivo (Wiedmeier et al, 1987) and in vitro (Newbold et al, 1996). Microbial conversion of peptides and amino acids to ammonia in the rumen is unfavourable to the host animal, because energy is required for microbial protein synthesis, and not all ammonia is incorporated into protein (Wallace et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have demonstrated no effects of yeast culture supplementation on ruminal pH, rumen ammonia concentration, and VFA patterns in vivo (Wiedmeier et al, 1987) and in vitro (Newbold et al, 1996). Microbial conversion of peptides and amino acids to ammonia in the rumen is unfavourable to the host animal, because energy is required for microbial protein synthesis, and not all ammonia is incorporated into protein (Wallace et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast cells are thought to stimulate bacterial growth through removal of oxygen that occurs in ruminal fluid at various times during the feeding cycle and in that way prevents the toxicity to the ruminal anaerobes (Chaucheyras-Durand et al, 2008). Yeast culture may also provide stimulatory factors for cellulolytic bacteria, such as B vitamins or branched-chain fatty acids (Weidmeier et al, 1987). On lysis, the yeast cells also provide protoplasm, which is a source of nutrition for the rumen microbes (Arambel and Kent, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Daniels Frumholtz et al (1989) (Boing 1983). Wiedmeier et al (1987) further suggested that yeast culture provided factors stimulatory toward proteolytic bacteria. In agreement with the present study, Frumholtz et al (1989) …”
Section: Discussionmentioning
confidence: 99%
“…Martin and Nisbet (1990) further reported that Aspergillus oryzae fermentation extract stimulated the in vitro mixed, ruminal microorganism fermentation of starch, bermudagrass and amino acids to different degrees. Other researchers reported increased dry matter (DM) and protein digestion (Wiedmeier et al 1987), increased fiber digestion (Gomez-Alarcon et al. 1990) and changes in rumen pH and volatile fatty acids (Harrison et al 1988;Martin et al 1989) when probiotics were fed to animals or added to in vitro ruminal fermentations.…”
mentioning
confidence: 99%